2020
DOI: 10.3390/d12090320
|View full text |Cite
|
Sign up to set email alerts
|

The Permeability of Natural versus Anthropogenic Forest Edges Modulates the Abundance of Ground Beetles of Different Dispersal Power and Habitat Affinity

Abstract: Forest edges are formed by natural or anthropogenic processes and their maintaining processes cause fundamentally different edge responses. We evaluated the published evidence on the effect of various edges on the abundance of ground beetles of different habitat affinity and dispersal power. Our results, based on 23 publications and 86 species, showed that natural forest edges were impenetrable for open-habitat species with high dispersal power, preventing their influx into the forest interiors, while forest s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…Open-habitat species with high dispersal power were significantly more abundant in natural edges than interiors, while became more similar in edges under anthropogenic interventions compared to their interiors. Contrary to this, the forest specialist species of limited dispersal power showed similar abundances in natural forest edges and interiors, but avoided edges influenced by agriculture or urbanisation (Magura & Lövei 2020b). In accordance with the history-based edge effect hypothesis (Magura et al 2017), our results clearly demonstrate, that the permeability (the filter function) of edges is essentially different depending on their history (maintaining processes) (Strayer et al 2003.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Open-habitat species with high dispersal power were significantly more abundant in natural edges than interiors, while became more similar in edges under anthropogenic interventions compared to their interiors. Contrary to this, the forest specialist species of limited dispersal power showed similar abundances in natural forest edges and interiors, but avoided edges influenced by agriculture or urbanisation (Magura & Lövei 2020b). In accordance with the history-based edge effect hypothesis (Magura et al 2017), our results clearly demonstrate, that the permeability (the filter function) of edges is essentially different depending on their history (maintaining processes) (Strayer et al 2003.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, in the present study, different habitat affinity could not explain the size-dependent permeability of natural edges. Interactions between the above life history (wing form) and ecological trait (habitat affinity) can be a meaningful indicator (Magura & Lövei 2020b) to test the size-dependent permeability of natural edges. The proportion of macropterous or dimorphic matrix (open-habitat and generalist) species was 64% for the small, 48% for the medium-sized, and 20% for the large species.…”
Section: Discussionmentioning
confidence: 99%
“…For forest specialist species, edges maintained by natural processes are penetrable, allowing these species to enter and cross the edges. However, edges created by urbanization are impenetrable, blocking the emigration of forest specialists from the forest fragments, contributing to even higher isolation of these species [97,98]. Similarly, the abundance of predatory ground beetles was higher in natural edges than their forest interiors, while no similar pattern was detected in edges sustained by urbanization.…”
Section: Effects Of Urbanization At the Ecosystem Levelmentioning
confidence: 98%
“…Management practices of urban habitats may alter the location and intensity of edge effects [96]. The abundance of forest specialist carabids was similar in edges maintained by natural processes and their interiors, while it was significantly lower in the edges than interiors of urban forest fragments [97,98]. The filtering function of variously maintained edges is fundamentally different.…”
Section: Effects Of Urbanization At the Ecosystem Levelmentioning
confidence: 99%
“…Magura (2017) and Roume et al (2011) found higher dispersal ability from forest species into open habitat than vice versa. However, permeability of forest edges by carabids is dependent on their history (Magura et al, 2017;Magura & Lövei, 2020). Although edges created through anthropogenic influence are penetrable for open habitat species, they are avoided by forest species (Magura & Lövei, 2020).…”
Section: Influence Of Habitat Type On Species Assemblagesmentioning
confidence: 99%